Multi-criteria methods applied in the studies of barriers identified in the implementation of reverse logistics of e-waste: A research agenda - Barbara Oliveira Vieira; Patricia Guarnieri; Rose Nofal; Bayram Nofal (Logistics, 2020)
Reverse logistics (RL) has emerged as a form of disposal and a conscious way to use products at the end of their use through the refurbishment, reuse, and recycling processes. Mainly in developing countries, there are still several barriers during the process of implementing reverse logistics, so decision-makers need to know what barriers to prioritize to propose a solution. This paper aims to investigate which multicriteria decision aid (MCDA) methods are most applied in the studies on barriers during the implementation of reverse logistics. For this purpose, we conducted a systematic literature review using a well-known and detailed protocol, considering various papers published in journals from the databases Science Direct, Emerald,Web of Science, and Google Scholar in the period from 2008 to 2019. As a result, a few studies discussing multicriteria methods were identified, analyzing the existing barriers to the implementation of reverse logistics. The main methods and criteria were gathered from the literature and were systematized and discussed to identify a research agenda. This paper contributes to the work carried out by researchers and practitioners in this field and can guide them in their choice of methods to approach decision-making related to reverse logistics.
Keywords: 650; barriers; multicriteria decision aid; reverse logistics